2014
DOI: 10.1186/s12933-014-0154-3
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase-4 inhibitor linagliptin attenuates neointima formation after vascular injury

Abstract: BackgroundRecently, glucagon-like peptide-1 (GLP-1)-based therapy, including dipeptidyl peptidase-4 (DPP-4) inhibitors and GLP-1 receptor agonists, has emerged as one of the most popular anti-diabetic therapies. Furthermore, GLP-1-based therapy has attracted increased attention not only for its glucose-lowering ability, but also for its potential as a tissue-protective therapy. In this study, we investigated the vascular-protective effect of the DPP-4 inhibitor, linagliptin, using vascular smooth muscle cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 37 publications
3
24
0
1
Order By: Relevance
“…Further elucidation of DPP-4 substrates is required. Furthermore, Kanasaki et al have recently reported that linagliptin inhibited the endothelial-to-mesenchymal transition in type 1 diabetic mouse kidney, independent of the glucose-lowering effect [37]. This pleiotropic effect could be a potential effect of linagliptin.…”
Section: Discussionmentioning
confidence: 96%
“…Further elucidation of DPP-4 substrates is required. Furthermore, Kanasaki et al have recently reported that linagliptin inhibited the endothelial-to-mesenchymal transition in type 1 diabetic mouse kidney, independent of the glucose-lowering effect [37]. This pleiotropic effect could be a potential effect of linagliptin.…”
Section: Discussionmentioning
confidence: 96%
“…Anti‐inflammatory effects of linagliptin were evidenced in vitro in mouse podocytes . This giptin showed impacts on improvement of vascular dysfunction in vascular tissues in mice and rats . It was reported to attenuate inflammatory processes in myocardium of mice, such as exert renoprotective effects in mice and rats …”
Section: Suppression Of Inflammatory Mediators and Pathways In Vasculmentioning
confidence: 99%
“…This polypeptide decreases MCP‐1 levels through protein kinase A (PKA) signaling what leads to the suppression of ERK and NF‐κB activation . Linagliptin at 3 mg/kg/day orally for 6 weeks reduced oxidative stress and attenuated vascular smooth muscle cells proliferation after vascular injury in mice . It, administered at 10 mg/kg per day orally for 20 weeks, attenuated expression of MCP‐1, VCAM‐1, and NADPH oxidase subunits in aoric atherosclerotic plaques and tended to decrease macrophage plaque infiltration in normoglycemic apolipoprotein E‐deficient mice .…”
Section: Suppression Of Inflammatory Mediators and Pathways In Vasculmentioning
confidence: 99%
“…DPP‐4 inhibitors have also been investigated using experimental restenosis models. In wild‐type mice, linagliptin suppresses neointimal hyperplasia after an arterial injury. In addition, the effect of DPP‐4is was examined in Otsuka Long‐Evans Tokushima fatty rats, which is a model of type 2 diabetes with insulin resistance.…”
Section: Incretins and Dpp‐4 Inhibitors Suppress Neointimal Hyperplasmentioning
confidence: 99%